Concerns about medications in patients with chronic respiratory disease - Kovačević, Milena; Ćulafić, Milica; Roganović, Maša; Jovanović, Marija; Vučićević, Katarina; Vezmar Kovačević, Sandra; Miljković, Branislava (Archives of Pharmacy, 2022)
Patients’ beliefs can significantly impact the adherence and outcomes of chronic disease therapy. The aim of the study was to assess the negative attitudes (concerns) of adult patients towards the use of medications for asthma and chronic obstructive pulmonary disease (COPD). The questionnaire included demographics, data on therapy, disease control (modified Medical Research Council-mMRC for COPD, and Asthma Control Test-ACT), and concerns (Beliefs about Medicines Questionnaire-BMQ). A five-point Likert scale was used (1-strongly disagree, to 5-strongly agree). Analysis was performed using SPSS software (ver. 27). The study included 145 patients, 80 COPD (55.2%) and 65 asthma (44.8%). Adequate disease control was observed in 42% (45% mMRC <2, 38.5% ACT≥20). The mean concern score was 14.7±4.2 (range 6–25). The score did not differ significantly between the patients with asthma and COPD, nor depending on the disease duration. Concerns about the regular use of medications were expressed by 55.9%, long-term consequences 44.1%, development of addiction 32.4%, lack of knowledge 29.7% and the impact on everyday life 24.1%. Literature data indicate a strong correlation between negative attitudes towards medications with a lower level of adherence. It can be assumed that these results contribute to poor disease control observed in our study (<50%). Patients’ counseling on the importance of regular use and the benefit/risk ratio of asthma and COPD medications can be a meaningful intervention in improving attitudes and therapy outcomes.